Coupled-cluster techniques for computational chemistry: The CFOUR program package - Matthews, Devin A.; Cheng, Lan; Harding, Michael E.; Lipparini, Filippo; Stopkowicz, Stella; Jagau, Thomas-C.; Szalay, Péter G.; Gauss, Jürgen; Stanton, John F. (The Journal of chemical physics, 2020)
An up-to-date overview of the CFOUR program system is given. After providing a brief outline of the evolution of the program since its inception in 1989, a comprehensive presentation is given of its well-known capabilities for high-level coupled-cluster theory and its application to molecular properties. Subsequent to this generally well-known background information, much of the remaining content focuses on lesser-known capabilities of CFOUR, most of which have become available to the public only recently or will become available in the near future. Each of these new features is illustrated by a representative example, with additional discussion targeted to educating users as to classes of applications that are now enabled by these capabilities. Finally, some speculation about future directions is given, and the mode of distribution and support for CFOUR are outlined.